Hermaphroditism in pig: a case related - Bersano, Josete Garcia; Farinha, Fernando Brazão Nunes; Macruz, Romeu; Portugal, Manuel Alberto da Silva Castro (Brazilian Journal of Veterinary Research and Animal Science, 1994)
A case of intersexuality in pig is presented. The animal shows a rudimentary penis and a skin plica, since the prepuce until the ani. The animal has two ovarium and only one testiclc in the abdominal cavity. The epididimus was short and flexioned. The uterus, vagina and vulva was absente and one of the Falopius tube exibit a hipoplasie size with esteril liquid colection inside it. No signs of cspermatogese was observed.